Implementation of a cascade training model to enhance emergency care capacity of healthcare workers during the COVID-19 outbreak in Uganda - Sulaiman Bugosera Wasukira; Carl Trevor Kambugu; Judith Nanyondo S; Emmanuel Candia; Stephen Emmanuel Aporu; Patricia Ikwaru; Racheal Kwagala; Andrew Kwiringira; Peter Mukiibi; Costance Murungi; Marek Ma; Celine Jacobs; et al. (African Journal of Emergency Medicine)
Introduction: The COVID-19 pandemic highlighted the gaps and the need to strengthen the emergency care system in Uganda. The Ugandan Ministry of Health implemented an emergency care capacity-building program during the COVID-19 pandemic response to improve COVID-19 case management in Uganda. We describe the curriculum development and rollout using a cascade model. Methods: In June 2021, the World Health Organisation (WHO) Hospital Emergency Unit Assessment Tool (HEAT) was used to assess emergency units and document existing capacity gaps in regional referral hospitals and general hospitals. The WHO Basic Emergency Care curriculum was modified to a training curriculum for emergency care principles for COVID-19 management. Training of trainers was conducted across 14 health regions in July and August 2021. The trainers trained cascaded the training through facility-based training during continuous professional development sessions. Results: Using the HEAT, 115 health facilities (14 regional and 101 general hospitals) were assessed. Only 31.3% (36/115) of the health facilities had a formal triage system. 53.5% (54/101) of general hospitals lacked non-rotating staff in the emergency unit. Some 511 healthcare workers from 205 facilities were trained as trainers, of whom 51.8% were nurses. The trainers trained cascaded the training to 3,550 healthcare workers. There was a significant difference between the overall median pre-test (71%) and median post-test (86.8%) scores of trainers trained (p<0.001). Conclusion: There was a general lack of emergency unit protocols and a shortage of fixed staff at the emergency units. The cascade model facilitated the dissemination of emergency care knowledge to seven times more healthcare workers than the trainers trained. This demonstrates the efficiency of this approach in knowledge dissemination and its ability to be replicated in other low resource settings.